110k views
3 votes
8)

Solve the system 2x + 5y = 7 and 3x + 4y = 6 by elimination. Which procedure produces opposite terms to eliminate x? Include
proper justification.
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the commutative property of addition
Multiply the first equation by 4 and multiply the second equation by -5.
This is justified by the commutative property of addition.
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the multiplication property of equality.
Multiply the first equation by 4 and multiply the second equation by -5.
This is justified by the multiplication property of equality

User Gorn
by
5.5k points

2 Answers

3 votes

Answer:

i did the assignment i hope this helps! :)

1.) a & b

2.) a

3.) c

Explanation:

Consider these chemical equations.

N2(g) + 3H2(g) → 2NH3(g)

C(s) + 2H2(g) → CH4(g)

4H2(g) + 2C(s) + N2(g) → 2HCN(g) + 3H2(g)

Which equation(s) do you need to reverse in order to calculate the overall equation for the formation of HCN and H2 from NH3 and CH4? Check all that apply.

N2(g) + 3H2(g) 2NH3(g)

C(s) + 2H2(g) CH4(g)

4H2(g) + 2C(s) + N2(g) 2HCN(g) + 3H2(g)

What must you do before adding the equations?

multiply the second equation by 2

multiply the first equation by 1/3

multiply the third equation by 1/2

What is the overall reaction equation?

the last option!!!!

NH3(g) + CH4(g) 3H2(g) + HCN(g)

User Venkatesh G
by
5.2k points
2 votes

Answer:

Multiply the first equation by 3 and multiply the second equation by -2.

This is justified by the multiplication property of equality

Explanation:

we have


2x+5y=7 ----> first equation


3x+4y=6 ----> second equation

step 1

Multiple the first equation by 3 both sides


3(2x+5y)=3(7) -----> by multiplication property of equality


6x+15y=21 ----> new first equation

step 2

Multiple the second equation by -2 both sides


-2(3x+4y)=-2(6) -----> by multiplication property of equality


-6x-8y=-12 ----> new second equation

step 3

Solve the system of equations by elimination

Adds new first equation and new second equation


6x+15y=21\\-6x-8y=-12\\-------\\15y-8y=21-12\\7y=9\\y=(9)/(7)

Find the value of x

substitute the value of y in any equation and solve for x


6x+15y=21


6x+15((9)/(7))=21


6x=21-(135)/(7)


6x=(12)/(7)


x=(2)/(7)

The solution is the point
((2)/(7),(9)/(7))

therefore

Multiply the first equation by 3 and multiply the second equation by -2.

This is justified by the multiplication property of equality

User Edwin Enriquez
by
5.1k points